Construction and evaluation of STZ-induced diabetes and diabetic kidney disease models in C57BL/6J mice - Li, Hao; Qin, Fang; Zheng, Shanshan; Wu, Jing; Lin, Sen; Gao, Xinyuan; Liu, Yipeng (Frontiers in Endocrinology, 2025)
ObjectiveTo explore the optimal strategy for streptozotocin (STZ)-induced models of diabetes mellitus (DM) and Diabetic kidney disease (DKD) in C57BL/6J mice, and to analyze potential factors influencing model stability.MethodsForty-five 6-week-old male C57BL/6J mice were randomly assigned to six groups: normal control (CON), unilateral nephrectomy control (CU), standard diet with STZ (CS), standard diet with unilateral nephrectomy and STZ (CUS), high-fat diet with STZ (HS), and high-fat diet with unilateral nephrectomy and STZ (HUS). Mice in the HS and HUS groups received a high-fat diet (HFD) for 6 weeks, followed by unilateral nephrectomy (UN) or sham surgery, and were then administered STZ (35 or 45 mg/kg/day, intraperitoneally) for five consecutive days to induce DM. DM induction was confirmed when two consecutive random blood glucose (RBG) measurements were ≥ereu mmol/L. Throughout the study, RBG, body weight, and urine albumin-to-creatinine ratio (UACR) were monitored longitudinally. At 19 weeks post-induction, mice were euthanized for kidney weight assessment and histopathological examination.ResultAll STZ-treated mice initially developed diabetes (100%); however, sustained hyperglycemia was not achieved in all cases. Glycemic stability was strongly influenced by the induction strategy (P<0.05). Specifically, 45 mg/kg/day STZ with a normal diet yielded only a 14.3% remission rate (2/14), whereas 35 mg/kg/day STZ with a HFD resulted in a 62.5% remission rate (10/16). Although 45 mg/kg/day STZ combined with a HFD maintained persistent hyperglycemia, it was accompanied by excessive mortality (80%, 8/10). UN was not associated with glycemic stability (P > 0.05); however, it markedly accelerated DKD progression and exhibited a synergistic effect with HFD. Furthermore, compared with mice exhibiting partial glycemic remission, those with stable hyperglycemia demonstrated significantly higher kidney weight, kidney-to-body weight ratio, and UACR (P<0.05).ConclusionAn appropriate dose of STZ in combination with UN and HFD represents an optimal strategy for establishing an STZ-induced DKD model in C57BL/6J mice, effectively recapitulating the clinical and pathological features of human DKD and providing a robust platform for mechanistic research and therapeutic development.